Primary Caregiver Perception of Pain Control following Pediatric Adenotonsillectomy: A Cross‐Sectional Survey. (3rd October 2016) - Sowder, Justin C.; Gale, Craig M.; Henrichsen, Jacob L.; Veale, Kristy; Liljestrand, Katie B.; Ostlund, Barbara C.; Sherwood, Aaron; Smith, Austin; Olsen, Griffin H.; Ott, Mark; Meier, Jeremy D.
Abstract : Objectives: To (1) review pain medications prescribed following pediatric adenotonsillectomy (T&A), (2) identify pain medications reported to be helpful, and (3) compare parent‐reported outcomes among various combinations of pain medications. Study Design: Case series with planned data collection. Setting: Multihospital network. Subjects and Methods: The primary caregivers of children aged 1 to 18 years who underwent isolated T&A from June to December 2014 were contacted 14 to 21 days after surgery. Data collected included pain medications prescribed, medications most helpful in controlling pain, and duration that pain medication was required. Parents rated their children's pain on postoperative days 2, 3, 7, and 14 and reported the time to resumption of normal diet/activity, as well as any hospital return visits. Results: The study cohort included 672 subjects of 1444 potential participants (46% response rate). The mean age of the patients was 7.9 ± 3.6 years. Narcotics were prescribed in 71.9%, and 70.4% were told to use ibuprofen. Children who took ibuprofen alone were significantly younger ( P <. 001). Pain was significantly less on postoperative days 2 and 3 in the ibuprofen‐only group as compared with the groups taking narcotics only ( P <. 001) and ibuprofen with narcotics ( P =. 002). Those taking ibuprofen alone returned to normal activity ( P <. 001) and diet ( P =. 026) sooner than those taking ibuprofen with narcotics. No difference was seen in pain control on subgroup analysis comparing oxycodone and hydrocodone. Conclusions: For pediatric T&A, significant variation exists in the management of postoperative pain. Parents of children given ibuprofen reported less pain than those given narcotics with and without ibuprofen. Further studies are needed to identify the optimal pain regimen for children after T&A.